Sterols and flavone from the leaves of Vernonia amygdalina growing in Thua Thien Hue - Tuan Anh, Hoang Le; Lien, Le Thi; Cuong, Pham Viet; Arai, Masayoshi; Ha, Tran Phuong; Dat, Ton That Huu; Cuong, Le Canh Viet (Vietnam Journal of Science and Technology, 2018)
By using various chromatographic methods, two sterols and one flavone, vernoniamygda A (1), vernoniamygda B (2), and luteolin (3) were isolated from the methanol extract of the leaves of Vernonia amygdalina. Their structures were determined using 1D, 2D-NMR and ESI-MS analysis as well as by comparison with the reported data. Compounds 1 and 2 were reported from natural for the first time.